ANALISIS MODEL PENGEMBANGAN KURIKULUM TAHFIDZ AL-QUR’AN DI MA’HAD AL-ULYA DALAM PERSPEKTIF AKSIOLOGIS - Wahid, Abdul; Alawiyah, Wiwi; Buna'i; Masrurah, Waqiatul (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2025)
Tahfidz Al-Qur'an education in Indonesia is rapidly growing, yet it often overlooks the internalization of values in favor of memorization quantity. This study aims to analyze the Tahfidz Al-Qur'an curriculum development model at Ma’had Al-Ulya from an axiological perspective to uncover its fundamental underlying values. Using a descriptive-exploratory qualitative approach, data were collected through interviews, observations, and documentation. The findings indicate that the applied curriculum model is an action research model, initiated as a solution to the decline in student interest. Axiological analysis identifies dominant values such as pragmatism, competition, balance, and adaptability. A significant tension was found between the extrinsic motivation driven by competition and the low intrinsic motivation (love for the Qur'an) which acts as an inhibiting factor. This study concludes that while effective, the model can be enhanced by strengthening intrinsic values like mahabbah (love) and ta'awun (mutual help) to create a more holistic Tahfidz education